Preoperational Thinking as a Measure of Social Cognition Is Associated With Long-Term Course of Depressive Symptoms. A Longitudinal Study Involving Patients With Depression and Healthy Controls - Sondermann, Stefan; Stahl, Jörg; Grave, Ulrike; Outzen, Janne; Moritz, Steffen; Klein, Jan Philipp (Frontiers in Psychiatry, 2020)
Background: Deficits in social cognition, referred to as preoperational thinking, are assumed to play a key role in the pathogenesis of persistent depression. The aim of this study was to explore the effect of preoperational thinking on the two-year course of depressive symptoms in a sample of persistently depressed, episodically depressed as well as healthy participants. Methods: We recruited 43 persistently depressed participants, 26 episodically depressed participants and 16 healthy control participants. Preoperational thinking was assessed at baseline with the Luebeck Questionnaire for Recording Preoperational Thinking. Over the period of two years, the course of depressive symptom severity was measured every three months using the Inventory of Depressive Symptomatology. Results: Using linear mixed model analysis we found a significant effect for the influence of preoperational thinking on the severity of depressive symptoms in the observation period. We found a non-significant statistical trend for an association of preoperational thinking with the change of depressive symptom severity. Conclusion: Our analyses suggest that a high degree of preoperational thinking is associated with a higher severity of depressive symptoms and possibly less symptom improvement. These findings support the notion that preoperational thinking is a relevant factor for the further course of depression and might indeed contribute to the maintenance of persistent depression.